A study on the compliance of radiopharmaceuticals good storage practice: are we following the international code of practice? - Paimon, Muhammad Fahriszaki; Baharudin, Mohamad Fauzanudin; Nik Afinde, Nik Muhammad Fitri (2009)
The main goal of Good Storage Practice (GSP) is to inform all organizations which involve in storage practice such as manufacturers, importers and wholesalers regarding Good Storage Practice in all conditions relating to appropriate and proper storage and also procedures in store management. This guideline acts as supplement to the existing guides by describing the special measures considered appropriate and available for the storage and transportation of pharmaceuticals. This prospective study was carried out to justify storage conditions in radiopharmaceutical department in Malaysia either they follow the standard guidelines in GSP or they neglect them for some reasons. These guides are precisely linked to other existing guides recommended by the WHO Expert Committee on Specifications for Pharmaceuticals Preparations which describes the special measures considered appropriate for the storage and transportation of pharmaceuticals in the world. During the study, the researchers selected a number of respondents which consist of personnel in radiopharmaceutical department in Hospital Putrajaya, Hospital Kuala Lumpur, and Malaysian Nuclear Agency and their knowledge on GSP mere assessed. Using a two-paged questionnaires form, the researchers distribute a comprehensive questionnaire about GSP to identify their understanding and to recognize existing adapted of GSP in their storage area. We also conducted a two-paged checklist form which is based on criteria in Annex 9 to supervise and monitor the conditions of storage, transportation and distribution of pharmaceuticals by face-to-face interview and observation. The criteria in GSP that researchers have been monitored included personnel aspect, premises and facilities, storage requirements, returned goods, dispatch and transport, and last but not least product recall. From the result, the researchers can conclude that all radiopharmaceutical facilities in Malaysia which have been selected for this study do not completely comply with the GSP standard in their storage management. Overall, the major weakness that has been noticed by the researchers in these three facilities and it should be emphasized in future is the management of the storage area. For instance, proper handling of outdated, rejected, and quarantine items. From the observation, the main problem is inadequate space and lack of knowledge in handling of them. Besides that, they should have adequate trained personnel and proper documentation in all aspects that have